Severe Congenital Factor X Deficiency in 5-Month-Old Child - Girolami, A; Molaro, G; Calligaris, A; De Luca, G (Thrombosis and Haemostasis, 1970)
A case of severe congenital factor X deficiency is presented. The patient was a 5 month old child who had several episodes of melena since the first weeks of life. Other bleeding manifestations were subcutaneous hematomas and a massive brain hemorrhage. The prothrombin time was severely prolonged and was corrected by normal serum, aged normal plasma and by the plasma of patients with parahemophilia, congenital hypoprothrombinemia and factor VII deficiency. On the contrary adsorbed normal plasma and Mr. Stuart’s plasma failed to correct the abnormality.The partial thromboplastin time, prothrombin consumption and the thromboplastin generation test were abnormal too. The T.G.T. was corrected by the substitution of the patient’s serum with normal serum. The factor X level was less then 0.1% of normal. All other clotting factors were within normal limits.Both parents of the “propositus” showed slightly decreased levels of factor X in their plasmas and were considered to be heterozygotes for the defect.